Effect of Numbered Heads Together Model on Student Motivation in Mathematics - Darwati Darwati; Fadly AS; Gilang Kurniawan; Laila Marhayati (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2026)
This study examines the effect of the Numbered Heads Together cooperative learning model on student motivation in mathematics. A quantitative approach with a quasi-experimental design was employed, involving 61 students divided into two groups: 33 in the experimental class taught using Numbered Heads Together and 28 in the control class taught with conventional methods. The sample was determined through cluster sampling. A mathematics learning motivation questionnaire served as the research instrument, tested for validity and reliability with Cronbach’s alpha of 0.915. Questionnaire scores were converted into interval scales using the Method of Successive Interval. Prerequisite analysis confirmed no significant differences in population data, with the Kruskal–Wallis test yielding p = 0.997 (> 0.05). Hypothesis testing using the independent t-test revealed a significant difference in learning motivation between the two groups (p = 0.002 < 0.05). The findings demonstrate that students taught with the Numbered Heads Together model exhibited higher motivation in mathematics compared to those taught conventionally. The strength of this model lies in fostering individual responsibility while promoting positive peer interaction, which directly enhances student motivation in mathematics.